Cytosolic DNA composition is determined by genomic instability mechanism and regulates dendritic cell-mediated anti-tumor immunity - Shayla R. Mosley; Angie Chen; David N.W. Doell; Siwon Choi; Courtney Mowat; Felix Meier-Stephenson; Vanessa Meier-Stephenson; Kristi Baker (Cell Reports)
Summary: Patients with colorectal cancers (CRCs) that have microsatellite instability (MSI) (MSI CRCs) face a better prognosis than those with the more common chromosomal instability (CIN) subtype (CIN CRCs) due to improved T cell-mediated anti-tumor immune responses. Previous investigations identified the cytosolic DNA (cyDNA) sensor STING as necessary for chemokine-mediated T cell recruitment in MSI CRCs. Here, we find that cyDNA from MSI CRC cells is inherently more capable of inducing STING activation and improves cytotoxic T cell activation by dendritic cells (DCs). Sequencing indicates that MSI cyDNA is enriched in microsatellites, which, upon DC uptake, induce anti-tumor immunity in a manner consistent with clinical MSI CRCs. DNA-damaging therapies also modulate cyDNA stimulation capacity, with radiation inducing larger cyDNA sizes and increased mitochondrial DNA content. Identifying highly stimulatory endogenous cyDNAs such as those in MSI CRCs will allow for optimized development of DNA-based STING agonist therapies to improve the responses of CIN CRCs with CIN to immunotherapies.